1986
DOI: 10.1093/ajcn/44.3.379
|View full text |Cite
|
Sign up to set email alerts
|

Plasma carnitine and renal-carnitine clearance during pregnancy

Abstract: This study assessed the time course of decrease in plasma carnitine during pregnancy and compared the renal clearance of carnitine during late pregnancy with nonpregnant women. As early as the 8th wk of pregnancy, the mean (+/- SD) value of total plasma-carnitine concentration in 19 women was significantly decreased from 39.0 +/- 6.3 to 32.8 +/- 4.6 mumol/l and the values continued to fall to 17.3 mumol/l by the 36th wk. The pattern was due to a fall in free-carnitine level; acylcarnitine remained unchanged. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
11

Year Published

1988
1988
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 14 publications
4
25
0
11
Order By: Relevance
“…The present study agrees with other studies ((Bargen-Lockner et al, 1981;Cederblad et al, 1985Cederblad et al, , 1986Genger et al, 1988;Marzo et al, 1994;Schoderbeck et al, 1995;Cho et al, 2003) in showing that plasma carnitine concentrations in women markedly decline during pregnancy. In our study, plasma Table 3 Concentration of g-butyrobetaine and 6-N-trimethyllysine in plasma of women receiving either a L-carnitine supplement (500 mg per day) or a placebo from the 12th week of gestation until delivery at various time points Table 2 Concentration of total carnitine, free carnitine and carnitine esters in plasma of women receiving either a L-carnitine supplement (500 mg per day) or a placebo from the 12th week of gestation until delivery at various time points carnitine concentration at delivery in the placebo group was approximately 40% lower than that at week 12 of pregnancy.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study agrees with other studies ((Bargen-Lockner et al, 1981;Cederblad et al, 1985Cederblad et al, , 1986Genger et al, 1988;Marzo et al, 1994;Schoderbeck et al, 1995;Cho et al, 2003) in showing that plasma carnitine concentrations in women markedly decline during pregnancy. In our study, plasma Table 3 Concentration of g-butyrobetaine and 6-N-trimethyllysine in plasma of women receiving either a L-carnitine supplement (500 mg per day) or a placebo from the 12th week of gestation until delivery at various time points Table 2 Concentration of total carnitine, free carnitine and carnitine esters in plasma of women receiving either a L-carnitine supplement (500 mg per day) or a placebo from the 12th week of gestation until delivery at various time points carnitine concentration at delivery in the placebo group was approximately 40% lower than that at week 12 of pregnancy.…”
Section: Discussionsupporting
confidence: 93%
“…Physiologically, plasma carnitine concentrations are strongly controlled by the renal excretion of carnitine (Rebouche and Seim, 1998). It has been found that urinary excretion of carnitine even declines during pregnancy and paralleled plasma carnitine concentrations (Cederblad et al, 1986;Marzo et al, 1994). Therefore, an increased renal excretion of carnitine can be ruled out as a possible reason for the low plasma carnitine concentrations during late pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphatidylcholine Even in normal pregnancies plasma carnitine levels at species are by far the most abundant component of delivery are decreased to about half of the concentrathe phospholipid fraction. Dipalmitoyl phosphatidylcho-tions seen in non-pregnant women (7)(8)(9)(10). As shown line (l,2-dipalmitoyl^72-glycero-3-phospho-choline) is for rats, maternal carnitine levels are also significantly mainly responsible for surface activity (1,2).…”
mentioning
confidence: 99%
“…Während der Schwangerschaft kommt es zu einem Abfall der Gesamtcarnitinkonzentration im Plasma bis hin zur Geburt. Daraus wurde geschlussfolgert, dass wäh-rend der Schwangerschaft ein erhöhter Carnitinumsatz erfolgt (Scholte et al 1978;Genger et al 1988aGenger et al , 1988bBargenLockner 1981;Cederblad et al 1986;Peulecke 1995). strum geschuldet sowie, wenn auch in geringerem Maße, der täglichen Abgabe mit der reifen Milch.…”
Section: Carnitinunclassified